(untitled) (Mwanga wa Lugha, 2019)
In December 2015, United Nation’s 8 Millennium Development Goals (MDGs) expired and were subsequently replaced by 17 Sustainable Development Goals (SDGs). Goal number 5 of the SDGs was to achieve gender equality and empower all women and girls by the year 2030. The UN laid down an action plan that would help achieve the SDGs. However, the UN action plan is silent about issues of language that cause gender inequality. Today, September 2018, it is three years since the SDGs were implemented. According to UN SDG reports of 2016, 2017 and 2018 (see UN 2016, 2017, 2018), Gender inequality still persists worldwide, thus depriving women and girls of their basic rights and opportunities. This paper examines differences in language use between the male and female gender and the effect on overall empowerment of women. It argues that issues of language use disadvantage women in their effort to achieve sociopolitical and economic parity with their male counterparts.